Pregunta
upstudy study bank question image url

Solve for \( u \) \[ -\frac{4}{(u+1)(u+5)}=-2+\frac{1}{u+5} \]

Ask by Tyler Mann. in the United States
Feb 13,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

The solutions are \( u = -\frac{1}{2} \) or \( u = -0.5 \).

Solución

Solve the equation \( -\frac{4}{(u+1)(u+5)}=-2+\frac{1}{u+5} \). Solve the equation by following steps: - step0: Solve for \(u\): \(-\frac{4}{\left(u+1\right)\left(u+5\right)}=-2+\frac{1}{u+5}\) - step1: Find the domain: \(-\frac{4}{\left(u+1\right)\left(u+5\right)}=-2+\frac{1}{u+5},u \in \left(-\infty,-5\right)\cup \left(-5,-1\right)\cup \left(-1,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(-\frac{4}{\left(u+1\right)\left(u+5\right)}\times \left(u+5\right)\left(u+1\right)=\left(-2+\frac{1}{u+5}\right)\left(u+5\right)\left(u+1\right)\) - step3: Simplify the equation: \(-4=-2u^{2}-11u-9\) - step4: Swap the sides: \(-2u^{2}-11u-9=-4\) - step5: Move the expression to the left side: \(-2u^{2}-11u-9-\left(-4\right)=0\) - step6: Subtract the numbers: \(-2u^{2}-11u-5=0\) - step7: Factor the expression: \(-\left(u+5\right)\left(2u+1\right)=0\) - step8: Divide the terms: \(\left(u+5\right)\left(2u+1\right)=0\) - step9: Separate into possible cases: \(\begin{align}&u+5=0\\&2u+1=0\end{align}\) - step10: Solve the equation: \(\begin{align}&u=-5\\&u=-\frac{1}{2}\end{align}\) - step11: Check if the solution is in the defined range: \(\begin{align}&u=-5\\&u=-\frac{1}{2}\end{align},u \in \left(-\infty,-5\right)\cup \left(-5,-1\right)\cup \left(-1,+\infty\right)\) - step12: Find the intersection: \(u=-\frac{1}{2}\) The solution to the equation \(-\frac{4}{(u+1)(u+5)}=-2+\frac{1}{u+5}\) is \(u=-\frac{1}{2}\) or \(u=-0.5\).

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve for \( u \) in the equation \[ -\frac{4}{(u+1)(u+5)}=-2+\frac{1}{u+5}, \] let's start by eliminating the fractions. We can do this by multiplying both sides by \( (u+1)(u+5) \): \[ -4 = -2(u+1)(u+5) + (u+1). \] Now let's expand the right side: \[ -2(u+1)(u+5) = -2(u^2 + 6u + 5) = -2u^2 - 12u - 10, \] and adding \( (u + 1) \): \[ -2u^2 - 12u - 10 + u + 1 = -2u^2 - 11u - 9. \] Set this equal to -4: \[ -4 = -2u^2 - 11u - 9. \] Next, we can move everything to one side of the equation: \[ 0 = -2u^2 - 11u - 9 + 4. \] This simplifies to: \[ 0 = -2u^2 - 11u - 5. \] Multiply through by -1 for easier calculation: \[ 0 = 2u^2 + 11u + 5. \] Now we apply the quadratic formula \( u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): Here \( a = 2, b = 11, c = 5 \): 1. Calculate the discriminant: \[ b^2 - 4ac = 11^2 - 4 \times 2 \times 5 = 121 - 40 = 81. \] 2. Now plug into the quadratic formula: \[ u = \frac{-11 \pm \sqrt{81}}{2 \times 2} = \frac{-11 \pm 9}{4}. \] This gives us two possible solutions: 1. \( u = \frac{-11 + 9}{4} = \frac{-2}{4} = -\frac{1}{2} \). 2. \( u = \frac{-11 - 9}{4} = \frac{-20}{4} = -5 \). Now, we have the solutions: \[ u = -\frac{1}{2} \quad \text{and} \quad u = -5. \] **Final Answer:** \[ u = -\frac{1}{2} \text{ or } u = -5. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad